2019
DOI: 10.3389/fmicb.2019.01877
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of HTLV-1 Infection by HIV-1 First- and Second-Generation Integrase Strand Transfer Inhibitors

Abstract: More than 10 million people worldwide are infected with the retrovirus human T-cell lymphotropic virus type 1 (HTLV-1). Infection phenotypes can range from asymptomatic to severe adult T-cell leukemia/lymphoma (ATLL) and HTLV-1-associated myelopathy. HTLV-1, like human immunodeficiency virus type 1 (HIV-1), is a blood-borne pathogen and viral infection happens in a similar fashion, with the major mode of transmission through breastfeeding. There is a strong correlation between time of infection and disease dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(59 citation statements)
references
References 66 publications
6
53
0
Order By: Relevance
“…Similarly, understanding the integrase (IN) enzyme of HTLV, and how it can be inhibited, will be a critical part of the effort to control HTLV infections. We recently reported that the first- and second-generation HIV INSTIs are effective at inhibiting HTLV-1 strand transfer in vitro and integration in tissue culture 9 . In this report, we have characterised several groups of INSTIs that have been reported to inhibit the replication of HIV 10 , 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, understanding the integrase (IN) enzyme of HTLV, and how it can be inhibited, will be a critical part of the effort to control HTLV infections. We recently reported that the first- and second-generation HIV INSTIs are effective at inhibiting HTLV-1 strand transfer in vitro and integration in tissue culture 9 . In this report, we have characterised several groups of INSTIs that have been reported to inhibit the replication of HIV 10 , 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Akin to HTLV-1 IN, the enzyme readily utilizes short, double-stranded oligonucleotide mimics of vDNA ends for integration ( Supplementary Fig. 2a, c) 14,18 . Formation of stable intasomes in vitro can be technically challenging, and often requires the presence of host factors and/or hyperactivating mutations 11,12,19 .…”
Section: Resultsmentioning
confidence: 99%
“…The model analysis suggested that co-infected individuals with both viruses will have smaller number of healthy CD4 þ T cells in comparison with HIV or HTLV-I monoinfected individuals. It was reported in [62] that no treatments exist for acute or chronic HTLV-I infection. However, antiviral treatments of HIV infection is currently used to suppress viral replication.…”
Section: Conclusion and Discussionmentioning
confidence: 99%